Analisis Kepuasan Konsumen Pada Resto Kemuning Di Kemuning Kecamatan Ngargoyoso Kabupaten Karanganyar - Fathoni, Muhammad Iqbal, Kussudiyarsana S.E., M.Si (2016)
The aim of This study is to examine the effect of service quality, product quality, emotion, price, and facilities to consumer satisfaction in Resto Kemuning. This research is quantitative. This research was conducted on costumers Resto Ngargoyoso kemuning in Kemuning subdistrict, Karanganyar. This studi use customer as sample in this research. This study applced probability sampling to as sampling method, data were collected through questionnaire. Testing instrument in this study using validity and reliability test which aims to determine the feasibility of a question in the questionnaire. Analysis of the data in this study using multiple linear analysis is reinforced by the classical assumption test and permanence test models. The results of this study indicate that the variable quality of service, product quality, emotional, price, and facilities have positive influence and significant to the variable Customer Satisfaction. Given this research it can be concluded that the quality of service, product quality, emotional, price, and amenities needed to create customer satisfaction in the purchase in Resto Kemuning Ngargoyoso District of Karanganyar .